A comparative study on nonlinear optical properties of zinc porphyrins analogs: Coordination atoms and group effects. Issue 11 (21st February 2023) - Hou, Na; Liu, Ting‐Ting; Fang, Xiao‐Hui
Abstract: Density functional theory (DFT) has been carried out to investigate the electronic characteristics, UV–VIS–NIR absorption spectra, and nonlinear optical (NLO) properties of two series of zinc porphyrin analogs (FPD‐N x and TPD‐N x, x = 0–4) with donor‐ π ‐donor frameworks. The design of these analogs is based on previously synthesized furan‐linked zinc porphyrins (FPDs) and thiophene‐linked zinc porphyrins (TPDs). It is noted that their electro‐optical features are sensitive to the numbers of N‐coordination atoms and the attached groups. A dramatic enhancement of static first and second hyperpolarizabilities ( β 0 and γ 0 ) occurs when two furan/thiophene rings are attached to the zinc porphyrin. Among the two series, FPD‐N3 and TPD‐N3 have the largest β 0 values of about 7600 a.u. The static γ 0 values of these complexes range from 0.41 × 10 6 to 1.79 × 10 6 a.u. The FPD‐N x has a larger γ 0 value than the corresponding TPD‐N x, but the γ 0 value of FPD‐N2 is close to that of TPD‐N2. In the dynamic NLO process, the electro‐optical Pockels effect, second harmonic generation, and electro‐optic Kerr effect can be enhanced at the wavelength of 1907 nm. This study provides a new strategy for the experimental design of high‐performance NLO materials. Abstract : The electronic and nonlinear optical properties of zinc porphyrins linked by furan/thiophene rings were investigated using density functional theory. The static first ( β 0 ) and second hyperpolarizability ( γ 0 ) are significantly enhanced when carbon atoms replace the coordinated N atoms of the porphyrin. In most cases, the β 0 / γ 0 value of the complex with furan units is larger than that of the corresponding complex with thiophene rings.